Prevalence of risk factors and of coronary artery disease, ischemic stroke, carotid arterial disease and lower extremity peripheral arterial disease in 96 patients undergoing elective surgery for an abdominal aortic aneurysm - Sule, Sachin (Pulsus Group Inc, 2008)
Ninety-six patients (77 men and 19 women), with a mean (± SD) age of 77±9 years, underwent elective surgery between 2006 and 2007 for an abdominal aortic aneurysm (AAA) greater than 5.5 cm in diameter. Of the 96 patients with an AAA, 31 (32%) were smokers, 85 (89%) had hypertension, 78 (81%) were treated with statins for hypercholesterolemia and 24 (25%) had diabetes mellitus. As well, 71 (74%) had coronary artery disease, 17 (18%) had a previous ischemic stroke, 19 (20%) had carotid arterial disease and 37 (39%) had peripheral arterial disease of the lower extremities.